Understanding the Crystallization of Pla Effects of Temperature and Shearing Conditions - Siginer, D (American Society of Mechanical Engineers, 2016)
Processing conditions of polymers governs the final part properties; in fact the thermomechanical history subjected by the polymer affects directly the crystalline microstructure and the crystallinity. In this work we aim to draw a global view about the crystallization kinetics and crystalline morphology of Polylactide (PLA). Unfortunately, the crystallization kinetics of PLA is very slow and limits the possibility to extend its application in several industrials domains. The enhancement of the PLA crystallization kinetic can be obtained by addition of nucleating agents of by ordering the molecular chains during flow, as in processing conditions. In this paper, we propose to highlight the competition between several parameters, as the shear rate, the temperature kinetics and the shearing time. Copyright © 2016 by ASME.